Anti-adhesive composition for unvulcanized rubber and its use
The anti-adhesive composition for unvulcanized rubber, comprising silicate, nonionic surfactant, and metal soap, addresses the limitations of existing agents by ensuring both effective adhesion resistance and disintegration, improving productivity in rubber processing.
Patent Information
- Application Number
- JP2020168180
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-10-05
- Publication Date
- 2024-12-16
- Estimated Expiration
- 2040-10-05
AI Technical Summary
Existing anti-adhesive agents for unvulcanized rubber either lack sufficient anti-adhesive properties or disintegration properties, or require high concentrations that lead to productivity issues and increased risk of forming lumps.
An anti-adhesive composition for unvulcanized rubber containing a silicate, a nonionic surfactant with HLB 3 to 13, metal soap, and/or wax, with specific ratios of iron compounds, to achieve both excellent adhesion resistance and disintegration properties.
The composition provides effective adhesion prevention and easy disintegration of dried solidified products, enhancing productivity by reducing sticking and lump formation during storage.
Smart Images

Figure 0007599890000001 
Figure 0007599890000002 
Figure 0007599890000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an anti-adhesive composition for unvulcanized rubber and its use. [Background technology]
[0002] In the production and processing of rubber products, unvulcanized rubber is sometimes stored in piles until it is moved to the next process such as molding or vulcanization. In this case, anti-adhesion agents (anti-adhesion agents) are used to prevent the rubber from sticking together. The most widely used anti-adhesive agents are those that contain inorganic powders and surfactants as their main components, and are generally applied to the rubber surface in the form of an aqueous dispersion and then dried. The application method is to spray the aqueous dispersion or to immerse the rubber surface in the aqueous dispersion.
[0003] In the production and processing of rubber products, unvulcanized rubber is sometimes stored in piles until it is moved to the next process such as molding or vulcanization. In this case, anti-adhesion agents (anti-adhesion agents) are used to prevent the rubber from sticking together. Anti-adhesives that are mainly composed of inorganic powders and surfactants are widely used, and are generally applied to the rubber surface in the form of an aqueous dispersion and then dried. As the inorganic powder, water-swellable inorganic powders such as bentonite are commonly used. Water-swellable inorganic powders swell in water and become fine particles, which gives them excellent adhesion to rubber. However, because they become fine particles, the cohesive force between the particles is strong when dried, and the hardness of the dried solidified product increases significantly. As a countermeasure to this problem, anti-adhesive agents that improve the disintegration properties of the dried and solidified product have been developed, but there has been no anti-adhesive agent that solves the above problems and satisfies all of the properties required of an anti-adhesive agent.
[0004] Patent Document 1 discloses an anti-adhesive composition comprising a water-soluble polymer having film-forming properties and an anionic or nonionic surfactant. This anti-adhesive composition is characterized by not using inorganic powder, and is capable of suppressing the formation of a dried solid. However, In order to achieve sufficient adhesion-prevention performance, it is necessary to use the composition at a high concentration. In that case, the water-soluble polymer has a significantly high water retention property, which makes the drying process after application of the adhesion-prevention composition time-consuming, thereby reducing productivity. Patent Document 2 discloses an adhesion inhibitor for rubber that is mainly made of a specific inorganic powder other than bentonite and has improved disintegrability of the dried solidified product. However, anti-adhesion agents that are not mainly made of water-swellable inorganic powder such as bentonite have poor adhesion, so they need to be used at high concentrations to obtain sufficient adhesion. At high concentrations, even if the disintegrability of the dried solidified product is improved, the risk of forming anti-adhesion agent lumps that become foreign matter on the rubber increases. As described above, anti-adhesive agents with improved disintegration properties are disclosed in Patent Documents 1 and 2, but at the same time, none of them satisfy sufficient anti-adhesive properties. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 62-32127 [Patent Document 2] Japanese Patent Application Publication No. 14-363532 Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide an adhesion-preventive composition for unvulcanized rubber that is excellent in both adhesion prevention and disintegration properties, and a method for producing unvulcanized rubber that has been treated with an adhesion prevention agent using the adhesion-preventive composition for unvulcanized rubber. [Means for solving the problem]
[0007] As a result of intensive research into solving the above-mentioned problems, the present inventors have found that the problems can be solved by an anti-adhesive composition for unvulcanized rubber, which contains a surfactant including a nonionic surfactant that exhibits a specific HLB value according to the Griffin method, an inorganic component including a specific iron compound, and a metal soap and / or wax. That is, the adhesion-preventive composition for unvulcanized rubber of the present invention is an adhesion-preventive composition for unvulcanized rubber containing an inorganic component, a surfactant, and a metal soap and / or wax, The inorganic component essentially contains a silicate and at least one selected from iron oxide and iron sulfide, and the silicate is present in an amount of 10 to 100 parts by weight of the adhesion preventive composition for unvulcanized rubber. 32.5 Weight part The total of the metal soap and / or the wax is 10 to 65 parts by weight. and the total weight ratio of the iron oxide and the iron sulfide to the total weight of the silicate, the iron oxide, and the iron sulfide is less than 2% by weight; The surfactant essentially contains a nonionic surfactant having an HLB value of 3 to 13 according to the Griffin method.
[0008] Charcoal It is preferred that the composition further contains an acid salt.
[0009] The method for producing adhesion-preventively treated unvulcanized rubber of the present invention includes a treatment step of adhering the above-mentioned adhesion-preventive composition for unvulcanized rubber to the surface of molded unvulcanized rubber. Effect of the Invention
[0010] The adhesion-preventive composition for unvulcanized rubber of the present invention is excellent in both adhesion prevention and disintegration properties, and therefore is excellent in productivity in the unvulcanized rubber production process. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] [Anti-adhesive composition for unvulcanized rubber] The anti-adhesive composition for unvulcanized rubber of the present invention is an anti-adhesive composition for unvulcanized rubber that contains an inorganic component essentially containing a silicate, a surfactant essentially containing a nonionic surfactant having an HLB value of 3 to 13 according to the Griffin method, and a metal soap and / or wax. Each component will be described in detail below.
[0012] [Inorganic components] The inorganic component is a component of a material that forms a coating on the surface of unvulcanized rubber and exhibits adhesion prevention properties. In the anti-adhesive agent for unvulcanized rubber of the present invention, the inorganic component contains silicate as an essential component. Silicates generally have a structure formed by linking silicate tetrahedra, each of which is formed by inserting one silicon atom into the gap in the center of a triangular pyramid formed by four oxygen atoms. Silicates are further classified into nesosilicates, solosilicates, cyclosilicates, inosilicates, phyllosilicates, tectosilicates, etc., depending on the linking method of the silicate tetrahedra, and the adhesion inhibitor for unvulcanized rubber of the present invention may use one or more of these silicates in combination.
[0013] Nesosilicates are classified as independent interlocking silicates (SiO4) 4- The basic composition is a structure represented by the chemical formula: The nesosilicate is not particularly limited, but examples thereof include olivine such as forsterite, fayalite, and manganese olivine, humite, garnets such as pyrope, almandine, spessartine, grossular, andradite, and uvarovite, and gadolinites such as datolite and sillimanite, and the like, and these may be used alone or in combination of two or more.
[0014] Solosilicates are classified as complex interlocking silicates (Si2O7) 6- and (SiO 16 ) 12- The basic composition is at least one selected from the structures represented by the chemical formula: The nesosilicate is not particularly limited, but examples thereof include epidote such as zoisite and clinozoisite, melilite such as akermanite and gehlenite, and pumpellyite such as vesuvianite, and the like, and these may be used alone or in combination of two or more. Cyclosilicates are classified as ring-linked silicates (Si3O9). 6- , (SiO 12 ) 8- , (SiO 18 ) 12- The basic composition is a structure represented by the chemical formula: The nesosilicate is not particularly limited, but examples thereof include benitoite, beryl, tourmaline such as ferroelectric, magnesite, and sphaerolite, and osumilite, and these may be used alone or in combination of two or more.
[0015] Inosilicates are classified as single-chain silicates (Si2O6) 4- , (Si3O9) 6- , (SiO 11 ) 6- , (SiO 15 ) 10- , (SiO 21 ) 14- The basic composition is a structure represented by the chemical formula: The inosilicate is not particularly limited, but examples thereof include pyroxenes such as diopside, clinoenstatite, enstatite, acmite, and spodumene, and amphibole such as anthophyllite, tremolite, glaucophane, and rhodonite, and these may be used alone or in combination of two or more.
[0016] Phyllosilicates are classified as layer-connected silicates and have a basic structure represented by the chemical formula SiO2. Examples of phyllosilicates include, but are not limited to, smectites such as montmorillonite, beidellite, nontronite, saponite, hectorite, sauconite, and stevensite; vermiculites such as di-vermiculite and tri-vermiculite; kaolinites such as halloysite, kaolin, endelite, dickite, nacrite, and chrysotile; talc; mica such as tetrasilylic mica; pyrophyllite; margarite; clintonite; mica minerals such as muscovite, biotite, phlogopite, synthetic mica, and fluorine mica; jamonites such as paragolite, phlogopite, lepidolite, and antigorite; chlorites such as dompatite, sudolite, cookite, clinochlore, chamosite, chlorite, and nanite; and piolite-palygorskite such as sepiolite and palygorskite. These may be used alone or in combination of two or more.
[0017] Tectosilicates are classified as silicates with a network structure, and have a basic structure represented by the chemical formula SiO2. There are no particular limitations on the tectosilicates, and examples of such tectosilicates include feldspars such as sanidine, albite, anorthite, and nepheline; zeolites such as leucite, scosite, and heulandite; and stilts, and these may be used alone or in combination of two or more.
[0018] The silicate contained in the inorganic component used in the present invention preferably contains a phyllosilicate, which can form a coating film with good water dispersibility and excellent adhesion resistance. Among them, it is preferable that the phyllosilicate is at least one selected from smectite, kaolinite, talc, and mica, since it forms a coating film with excellent adhesion resistance.
[0019] When smectite comes into contact with water, the water molecules are successively hydrated with the exchangeable cations between the layers, causing the smectite to swell, and therefore it can be effectively dispersed in water. Therefore, it is more preferable that the phyllosilicate is smectite, since it has excellent dispersibility when mixed with water and improves the film forming properties. Among smectites, montmorillonite is preferable because it has particularly remarkable water swelling properties.
[0020] Montmorillonite is a dioctahedral hydrous layered silicate mineral that contains sodium, calcium, potassium, magnesium, hydrogen ions, etc. as exchangeable cations. These cations are easily exchangeable and also have the property of absorbing water easily. When the exchangeable cation is sodium ion, it easily absorbs water molecules due to hydration force, and the layer spacing increases, causing significant swelling.
[0021] Generally, a layered clay mineral containing montmorillonite as a main component is called bentonite. Bentonite is an example of an inorganic component, and can easily adsorb to the surface of unvulcanized rubber to form a coating. The coating of bentonite has excellent adhesion prevention and slip properties, so it is more preferable that the silicate in the adhesion prevention agent for unvulcanized rubber of the present invention contains bentonite as an essential component. In addition, when the bentonite contains sodium bentonite with high purity, the effect of water swelling is remarkable, which is the most preferable.
[0022] In addition, the inorganic components used in the present invention preferably have a low weight ratio of iron oxide and iron sulfide relative to the total of silicate, iron oxide and iron sulfide. Silicates are often present together with trace amounts of carbonates and iron compounds, but iron compounds have a high specific gravity compared to silicates and are not excellent in water dispersibility. Therefore, if the weight ratio of iron compounds relative to the total of silicate, iron oxide and iron sulfide is high, it will prevent the silicate from being uniformly attached to the rubber, causing deterioration of adhesion prevention. Therefore, from the viewpoint of promoting uniform attachment of the adhesion prevention agent and improving adhesion prevention, it is preferable to have as low a weight ratio of iron compounds as possible.
[0023] The weight ratio of iron oxide and iron sulfide to the total of silicate, iron oxide and iron sulfide is preferably less than 2%, more preferably less than 1.8%, even more preferably less than 1.6%, particularly preferably less than 1.4%, and most preferably less than 1.2%.
[0024] A preferred lower limit for the weight ratio of iron oxide and iron sulfide to the total of silicate, iron oxide and iron sulfide is 0.1% by weight, more preferably 0.05% by weight, even more preferably 0.01% by weight, still more preferably 0.001% by weight, particularly preferably 0.0001% by weight, and most preferably greater than 0% by weight.
[0025] As a method for adjusting the weight ratio of iron oxide and iron sulfide to the total of silicate, iron oxide, and iron sulfide, a commercially available silicate containing a coexisting iron compound at a weight ratio of less than 2% by weight can be obtained, but a silicate containing a coexisting iron compound may be subjected to a process such as centrifugation or centrifugal separation, or an iron compound may be mixed with the silicate. The iron compound in the present invention is at least one selected from iron oxide and iron sulfide, and may contain both.
[0026] [Method of Analyzing Weight Percentage of Iron Compounds] The weight percentage of iron compounds present together with silicates is measured by powder X-ray diffraction. When the measured value is below the detection limit, it is recorded as 0% by weight. Furthermore, there are no particular limitations on the average particle size of the inorganic component, but taking into consideration the adhesion to unvulcanized rubber, etc., it is preferably 0.1 to 200 μm, more preferably 0.1 to 100 μm, even more preferably 0.1 to 50 μm, particularly preferably 0.1 to 40 μm, and most preferably 0.1 to 30 μm.
[0027] The weight ratio of the silicate to the total weight of the adhesion-preventive composition for unvulcanized rubber is preferably 10 to 35 parts by weight, more preferably 12.5 to 32.5 parts by weight, and particularly preferably 15 to 30 parts by weight, when the adhesion-preventive composition for unvulcanized rubber is taken as 100 parts by weight.
[0028] [Surfactant] The surfactant is an essential component of the present invention and is a component that aids in the adhesion of the adhesion-preventive composition to unvulcanized rubber. By including a surfactant in the adhesion-preventive composition for unvulcanized rubber of the present invention, the adhesion to unvulcanized rubber is improved, and a film is formed more uniformly on the surface of the unvulcanized rubber, improving adhesion prevention.
[0029] The surfactant used in the present invention essentially contains a nonionic surfactant having an HLB value, as determined by the Griffin method, of 3 to 13. The nonionic surfactant improves the adhesion of the anti-adhesive composition to unvulcanized rubber.
[0030] Here, the HLB value according to the Griffin method is a value that can be calculated based on the molecular structure according to the following (I). That is, the HLB value according to the Griffin method ranges from 0 to 20, with a smaller value indicating greater lipophilicity and a larger value indicating greater hydrophilicity. HLB = 20 × (sum of formula weights of hydrophilic parts / molecular weight) (I) The nonionic surfactant having an HLB value of 3 to 13 according to the Griffin method is not particularly limited, and one or more types may be contained. The role of the nonionic surfactant having an HLB value of 3 to 13 according to the Griffin method is to form a wavy anti-adhesive film on the rubber surface by generating scum during circulation of the dispersion of the anti-adhesive agent containing silicate and metal soap and / or wax. If the HLB value according to the Griffin method is less than 3, the wettability to rubber is insufficient, and if it exceeds 13, the foam-inhibiting properties are insufficient. The HLB value according to the Griffin method is preferably from 4 to 12, more preferably from 5 to 11, and particularly preferably from 6 to 10, from the viewpoints of adhesion prevention and disintegration properties.
[0031] As the nonionic surfactant having an HLB value of 3 to 13 according to the Griffin method, for example, a nonionic surfactant represented by the following chemical formula (1) can be used. RO-(AO)nH (1) In the chemical formula (1), R is an aliphatic hydrocarbon group. The aliphatic hydrocarbon group may be linear or branched. The aliphatic hydrocarbon group may be either a saturated aliphatic hydrocarbon group or an unsaturated aliphatic hydrocarbon group. AO represents an oxyalkylene group having 2 to 4 carbon atoms, and n is the average number of moles of AO added.
[0032] The oxyalkylene group having 2 to 4 carbon atoms is, for example, a polymerization unit formed by addition of an alkylene oxide having 2 to 4 carbon atoms. When multiple types of oxyalkylene groups are contained, these groups may be arranged in a block form or random form. The weight ratio of the surfactant to the total weight of the anti-adhesive composition for unvulcanized rubber is not particularly limited, but from the viewpoints of adhesion and foaming of the aqueous dispersion, it is preferably 1 to 30% by weight, more preferably 1 to 28% by weight, particularly preferably 1 to 26% by weight, and most preferably 1 to 24% by weight.
[0033] [Metal soap] Metal soap is a component that adheres to the surface of unvulcanized rubber to reduce friction between unvulcanized rubber particles. It also weakens the cohesion of the dried solidified adhesion inhibitor and improves disintegration. Examples of metal soaps include magnesium laurate, calcium laurate, zinc laurate, magnesium myristate, calcium myristate, zinc myristate, magnesium palmitate, calcium palmitate, zinc palmitate, magnesium stearate, calcium stearate, zinc stearate, aluminum trioctadecanoate, aluminum dioctadecanoate, aluminum monooctadecanoate, calcium octadecanoate, zinc octadecanoate, magnesium octadecanoate, and barium octadecanoate. The metal soap is preferably at least one selected from magnesium stearate, calcium stearate, and zinc stearate, as this is highly effective in reducing friction between unvulcanized rubbers. The weight ratio of the metal soap to the total weight of the adhesion-preventive composition for unvulcanized rubber is preferably 10 to 70 parts by weight, more preferably 12.5 to 67.5 parts by weight, and particularly preferably 15 to 65 parts by weight, per 100 parts by weight of the adhesion-preventive composition for unvulcanized rubber, from the viewpoint of achieving the effects of the present invention.
[0034] The average particle size of the metal soap is not particularly limited, but from the viewpoints of friction reducing effect, disintegration improving effect, and powder falling off of the metal soap adhered to the surface of the unvulcanized rubber, it is preferably 0.1 to 200 μm, more preferably 0.1 to 100 μm, even more preferably 0.1 to 50 μm, particularly preferably 0.1 to 40 μm, and most preferably 0.1 to 30 μm.
[0035] [wax] Wax, like metal soap, adheres to the surface of unvulcanized rubber and reduces friction between unvulcanized rubber particles. It also weakens the cohesion of the dried and solidified adhesion inhibitor and improves its disintegration. The wax is not particularly limited, but examples thereof include particles made of vegetable wax, animal wax, mineral wax, petroleum wax, synthetic hydrocarbon wax, modified wax, hydrogenated wax, fatty acid amide, and phthalic anhydride imide, and one or more types may be used in combination.
[0036] The vegetable wax is not particularly limited, but examples thereof include candelilla wax, carnauba wax, rice wax, Japan wax, jojoba oil, sugar wax, bayberry wax, ocully wax, and esparto wax. The animal wax is not particularly limited, but examples thereof include beeswax, lanolin, spermaceti, insect wax, shellac wax, and the like. The mineral wax is not particularly limited, but examples thereof include montan wax, ozokerite, and ceresin. The petroleum wax is not particularly limited, but examples thereof include paraffin wax, microcrystalline wax, petrolatum, and the like. The synthetic hydrocarbon wax is not particularly limited, but examples thereof include Fischer-Tropsch wax and polyethylene wax. The modified wax is not particularly limited, but examples thereof include montan wax derivatives, paraffin wax derivatives, and microcrystalline wax derivatives.
[0037] The hydrogenated wax is not particularly limited, but examples thereof include hydrogenated castor oil, 12-hydroxystearic acid, 12-hydroxystearic acid amide, N-hydroxyethyl-12-hydroxystearylamide, N,N'-ethylene-bis-12-hydroxystearylamide, N,N'-hexamethylene-bis-12-hydroxystearylamide, N,N'-xylylene-bis-12-hydroxystearylamide, methyl-12-hydroxystearate, propylene glycol-mono-12-hydroxystearate, and ethylene glycol-mono-12-hydroxystearate. The fatty acid amide is not particularly limited, but examples thereof include lauric acid amide, stearic acid amide, oleic acid amide, erucic acid amide, N,N'-xylylenebisstearic acid amide, coconut oil fatty acid monoethanolamide, N-oleylstearic acid amide, and N,N'-dioleyl adipic acid amide. Among the waxes described above, at least one selected from vegetable waxes, petroleum waxes, synthetic hydrocarbon waxes, and hydrogenated waxes is preferred. With respect to the weight ratio of the wax to the total weight of the adhesion-preventive composition for unvulcanized rubber, from the viewpoint of achieving the effects of the present invention, the weight ratio of the wax is preferably 10 to 70 parts by weight, more preferably 12.5 to 67.5 parts by weight, and particularly preferably 15 to 65 parts by weight, per 100 parts by weight of the adhesion-preventive composition for unvulcanized rubber.
[0038] The average particle size of the wax is not particularly limited, but from the viewpoints of the effect of reducing friction, the effect of improving disintegrability, and powdering off of the wax, it is preferably 0.1 to 200 μm, more preferably 0.1 to 100 μm, even more preferably 0.1 to 50 μm, particularly preferably 0.1 to 40 μm, and most preferably 0.1 to 30 μm.
[0039] The adhesion inhibitor composition for unvulcanized rubber of the present invention may further contain the following components in addition to the components explained above. [Other inorganic components] The other inorganic components are components that adhere to the surface of the unvulcanized rubber to prevent adhesion between particles of the unvulcanized rubber and reduce friction between particles of the unvulcanized rubber. Other inorganic powders include, for example, carbonates such as calcium carbonate, sodium carbonate, and magnesium carbonate; sulfates such as calcium sulfate and barium sulfate; metal oxides such as amorphous silica, alumina, magnesium oxide, antimony trioxide, titanium oxide, and white carbon; metal hydroxides such as aluminum hydroxide, magnesium hydroxide, and iron hydroxide; red iron oxide; carbon black; and graphite. The other inorganic component is preferably a carbonate, and more preferably at least one selected from calcium carbonate, which is highly effective in reducing friction between unvulcanized rubbers, and sodium carbonate and magnesium carbonate, which promote swelling of bentonite in water and further improve adhesion prevention.
[0040] [Anionic Surfactants] Examples of anionic surfactants include fatty acid soaps such as potassium caprate, sodium caprate, sodium laurate, potassium laurate, sodium palmitate, potassium plumitate, potassium stearate, sodium stearate, sodium palm kernel oil fatty acid, potassium palm kernel oil fatty acid, potassium palm stearate, sodium palm stearate, sodium coconut oil fatty acid, potassium coconut oil fatty acid, sodium tallow fatty acid, and potassium tallow fatty acid; alkyl sulfates such as sodium lauryl sulfate, ammonium lauryl sulfate, sodium stearyl sulfate, and sodium cetyl sulfate; polyoxyalkylene alkyl ether acetates such as sodium polyoxyethylene tridecyl ether acetate; alkyl benzene sulfonates such as sodium dodecyl benzene sulfonate; polyoxyalkylene alkyl ether acetates ... long-chain sulfosuccinates such as sodium dioctyl sulfosuccinate, sodium 2-ethylhexyl sulfosuccinate, etc.; N-acyl sarcosine salts such as sodium oleoyl sarcosine, sodium lauroyl sarcosine, etc.; higher fatty acid amide sulfonates such as sodium stearoyl methyl taurate, sodium lauroyl methyl taurate, sodium myristoyl methyl taurate, sodium palmitoyl methyl taurate, etc.; alkyl phosphates such as sodium monostearyl phosphate; polyoxyalkylene alkyl ether phosphate salts such as sodium polyoxyethylene oleyl ether phosphate, sodium polyoxyethylene stearyl ether phosphate, etc.; long-chain N-acyl glutamates such as sodium monosodium N-lauroyl glutamate, disodium N-stearoyl-L-glutamate, etc.
[0041] [Water-soluble polymer] The water-soluble polymer is a component that imparts viscosity to the aqueous dispersion of the adhesion-preventive composition for unvulcanized rubber and improves the adhesion to the surface of unvulcanized rubber. The water-soluble polymer is not particularly limited, and examples thereof include starches such as oxidized starch, starch acetate, starch phosphate, carboxymethyl starch, carboxyethyl starch, hydroxyethyl starch, cationic starch, cyanoethylated starch, and dialdehyde starch; mannan; alginic acids such as alginic acid, sodium alginate, propylene glycol alginate, triethanolamine alginate, and ammonium alginate; methylcellulose, ethylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, and hydroxypropylmethylcellulose. Examples of water-soluble gums include cellulose ethers such as cellulose, hydroxyethyl methylcellulose, hydroxyethyl ethyl cellulose, and carboxymethyl cellulose; natural gums such as taracant gum, gum arabic, guar gum, xanthan gum, British gum, glucomannan, gellan gum, tara gum, locust bean gum, and carrageenan; sodium polyacrylate; polyvinyl alcohol; polyethylene glycol; polyethylene oxide; water-soluble acrylic resins; water-soluble urethane resins; water-soluble melamine resins; water-soluble epoxy resins; water-soluble butadiene resins; and water-soluble phenolic resins.
[0042] [Polyhydric alcohol] The polyhydric alcohol is a component that adheres to the surface of unvulcanized rubber, imparts lubricity to the unvulcanized rubber particles, and reduces friction between the unvulcanized rubber particles. The polyhydric alcohol is not particularly limited, and examples thereof include glycerin, 1,3-butanediol, propylene glycol, dipropylene glycol, pentylene glycol, neopentyl glycol, hexylene glycol, polyethylene glycol, erythritol, pentaerythritol, dipentaerythritol, trimethylolethane, trimethylolpropane, ditrimethylolpropane, xylitol, sorbitol, mannitol, maltitol, maltotriose, glucose, sucrose, fructose, maltose, and the like, and one or more of these may be used in combination.
[0043] [Antifoaming agent] Examples of the defoaming agent include silicone-based defoaming agents such as polymethylsiloxane and polyether-modified silicone; oil-based defoaming agents such as castor oil, sesame oil, linseed oil, and animal and vegetable oils; fatty acid-based defoaming agents such as stearic acid, oleic acid, and palmitic acid; fatty acid ester-based defoaming agents such as isoamyl stearate, distearyl succinate, ethylene glycol distearate, and butyl stearate; polyoxyalkylene monohydric alcohol di-t-amylphenoxyethanol, 3-heptanol, 2-ethylhexyl ether, and the like. Examples of such defoamers include alcohol-based defoamers such as xanol; ether-based defoamers such as di-t-amylphenoxyethanol, 3-heptyl cellosolve, nonyl cellosolve, and 3-heptyl carbitol; phosphate-based defoamers such as tributyl phosphate and tris(butoxyethyl) phosphate; amine-based defoamers such as diamylamine; amide-based defoamers such as polyalkylene amide and acylate polyamine; sulfate-based defoamers such as sodium lauryl sulfate; polyoxyalkylene-based defoamers; and mineral oil.
[0044] [Preservatives] Examples of preservatives include thiazoles such as thiazole and 2-mercaptothiazole; thiocyanates such as methylene bisthiocyanate and ammonium thiocyanate; sulfimides such as o-benzoic sulfimide and phenylmercuric-o-benzoic sulfimide; alkyl dialkyl thiocarbamates such as methyl dimethyl thiocarbamate and ethyl diethyl dithiocarbamate; thiuram sulfides such as tetramethyl thiraum sulfide and tetraethyl thiraum sulfide; thiuram disulfides such as tetramethyl thiraum disulfide and tetraethyl thiraum disulfide; dithiocarbamates such as ferric diethyl dithiocarbamate and lead dimethyl dithiocarbamate; sulfamides such as o-toluenesulfonamide and benzenesulfonanilide; 1-aminonaphthyl-4-sulfonamide, ... aminosulfonic acids such as 1-amino-2-naphthol-4-sulfonic acid; phenols such as pentachlorophenol and o-phenylphenol and their alkali metal salts; chlorinated quinones such as tetrachloro-p-benzoquinone and 2,3-dichloro-1,4-naphthoquinone; nitro group-containing compounds such as dinitrocaprylphenyl crotonate and dinitro-o-cresol; triazines such as 1,3,5-trihydroxyethylhexahydro-1,3,5-triazine and 1,3,5-triethylhexahydro-1,3,5-triazine; organic mercury compounds such as phenylmercuric phthalate and o-hydroxyphenylmercuric chloride; amines such as p-aminoazobenzene and diphenylamine; amides such as cinnamanilide; and iodine-containing compounds such as 1,3-diiodo-2-propanol.
[0045] 〔water〕 The water may be any of tap water, ion-exchanged water, distilled water, etc., and is not particularly limited, but is preferably ion-exchanged water, distilled water, etc. From the viewpoint of water hardness, soft water is preferable from the viewpoint of quality control.
[0046] [Method for producing anti-adhesive agent for unvulcanized rubber] The method for producing the adhesion-preventive agent for unvulcanized rubber of the present invention is not particularly limited with respect to the mixing order, mixing equipment to be used, etc., as long as it includes a step of mixing inorganic powder, surfactant, metal soap or wax, and other components, etc. The adhesion-preventive agent for unvulcanized rubber can be produced, for example, by sequentially adding each component to a powder mixer such as a ribbon-type mixer and mixing them.
[0047] [Method for producing anti-adhesive treated unvulcanized rubber] The method for producing an adhesion-preventive treated unvulcanized rubber of the present invention includes a treatment step of adhering the adhesion-preventive composition for unvulcanized rubber to the surface of the unvulcanized rubber. Here, the unvulcanized rubber is preferably one that has been molded. In the treatment step, a wet method, that is, a method using an aqueous dispersion in which water is blended as an anti-adhesive composition for unvulcanized rubber, is preferred. When the treatment step is performed by the wet method, the method of spraying the anti-adhesive composition for unvulcanized rubber (aqueous dispersion), the method of spraying the rubber with a thin stream, the method of immersing in the dispersion, etc. can be mentioned. The method of immersing in the aqueous dispersion is preferable because the anti-adhesive composition for unvulcanized rubber can be uniformly attached. The unvulcanized rubber used in the production method of the present invention is usually in a heated state at 100 to 180 ° C., and the unvulcanized rubber can be cooled by immersing in the aqueous dispersion. The temperature of the aqueous dispersion is not particularly limited, but is preferably 0 to 60 ° C. Next, a step of drying the unvulcanized rubber after the aqueous dispersion is attached may be performed. The drying method is not particularly limited, but a method of forcibly drying by blowing hot air with a hot air blower or blow heater is preferable because it is inexpensive. The concentration of the aqueous dispersion is preferably 0.01 to 10%, more preferably 0.05 to 7.5%, and even more preferably 0.1 to 5.0%, from the viewpoint of easily exhibiting good adhesion prevention and drying properties. If the concentration is less than 0.01%, the adhesion prevention properties may deteriorate, and if the concentration exceeds 10%, the drying properties may deteriorate. In the treatment step, a dry method, that is, a method using an anti-adhesive composition for unvulcanized rubber that does not contain water, may be used. The anti-adhesion treated unvulcanized rubber produced in this manner can be prevented from sticking to each other when it is stacked and stored until it is moved to the next process. EXAMPLES
[0048] The present invention will be specifically described below with reference to examples and comparative examples. The present invention is not limited to these examples. The physical properties in the examples and comparative examples were evaluated as follows.
[0049] [Adhesion resistance] An NR / BR test piece (natural rubber / butadiene rubber; 0.5 cm thick x 5 cm long x 3 cm wide) heated to 100°C is immersed in an aqueous dispersion (2.0% concentration) of an anti-adhesive composition for unvulcanized rubber and immediately removed. Two immersed rubber test pieces are prepared, air-dried, stacked, and subjected to a 1000 kg / m 2 A load of 10 ... Peel resistance of 1N / cm or less: Very good adhesion resistance (unvulcanized rubber can be easily peeled off from each other, the index is ◎) Peel resistance is over 1N / cm and less than 2N / cm: Good adhesion prevention (unvulcanized rubber can be peeled off from each other without load, index is ○) Peel resistance is between 2N / cm and 3N / cm: poor adhesion resistance (the load when peeling unvulcanized rubber from each other is large, adhesion resistance is low, and the index is △) Peel resistance exceeds 3N / cm: Very poor adhesion resistance (rubbers are in close contact with each other and are difficult to peel off. Very poor adhesion resistance, index is ×)
[0050] [Collapseability] The aqueous dispersion of the anti-adhesive composition for unvulcanized rubber was concentrated to dryness to prepare a 10 mm square dried solid. The hardness of each dried solid was measured with a durometer, and a value of less than 70 was deemed to be acceptable. Value less than 60: Very good disintegrability (dried solidified material disintegrates easily, index is ◎) Value is 60 or more but less than 70: Disintegrability is good (dried solidified material disintegrates, index is ○) Value between 70 and 80: poor disintegrability (dried solidified material is slightly difficult to disintegrate, index is △) Values over 80 or not measurable: Disintegrability is very poor (dried solids are difficult to disintegrate, index is ×)
[0051] Example 1 20 g of bentonite 1, 60 g of zinc stearate, and 20 g of POE(3) tridecyl ether were uniformly mixed to obtain an anti-adhesive agent for unvulcanized rubber. Next, 6 g of the above anti-adhesive composition was added to 294 g of tap water and uniformly dispersed in the water to obtain an aqueous dispersion of the anti-adhesive composition for unvulcanized rubber. The obtained aqueous dispersion was used to evaluate the anti-adhesive property and anti-falling property. The evaluation results are shown in Table 1, and the anti-adhesive property and disintegration property were excellent.
[0052] (Examples 2 to 16) In Examples 2 to 16, aqueous dispersions of anti-adhesive compositions for unvulcanized rubber were obtained and evaluated in the same manner as in Example 1, except that the compositions were changed as shown in Tables 1 and 2. The evaluation results are shown in Tables 1 and 2. Comparative Example 1 20 g of Bentonite 5, 60 g of zinc stearate, and 20 g of POE(3) tridecyl ether were uniformly mixed to obtain an anti-adhesive agent for unvulcanized rubber. Next, 6 g of the above anti-adhesive composition was added to 294 g of tap water and uniformly dispersed in the water to obtain an aqueous dispersion of an anti-adhesive composition for unvulcanized rubber. The obtained aqueous dispersion was used to evaluate the anti-adhesive property and disintegration property. The evaluation results are shown in Table 3, and the anti-adhesive property was poor.
[0053] (Comparative Examples 2 to 9) In Comparative Examples 2 to 9, aqueous dispersions of anti-adhesive compositions for unvulcanized rubber were obtained and evaluated in the same manner as in Comparative Example 1, except that the compositions were changed as shown in Table 3. The results are shown in Table 3. In the above examples and comparative examples, POE(m) means polyoxyethylene (the number of repeating oxyethylene units is m), and POP(n) means polyoxypropylene (the number of repeating oxypropylene units is n). The type of iron compound contained in the silicate used and the weight ratio of the iron compound to the silicate are as follows: Bentonite 1: 0.1% iron oxide by weight, 99.9% silicate by weight Bentonite 2: 0.5% iron oxide by weight, 99.5% silicate by weight Bentonite 3: 1% iron oxide and iron sulfide by weight, 99% silicate by weight Bentonite 4: 2% iron oxide and iron sulfide by weight, 98% silicates by weight Kaolin: 0.1% by weight of iron oxide, 99.9% by weight of silicate
[0054] [Table 1]
[0055] [Table 2]
[0056] [Table 3]
[0057] As can be seen from Tables 1 and 2, the adhesion-preventive compositions for unvulcanized rubber of Examples 1 to 16 are adhesion-preventive compositions for unvulcanized rubber containing an inorganic component, a surfactant, and a metal soap and / or wax, the inorganic component essentially containing a silicate and at least one selected from iron oxide and iron sulfide, the silicate is 10 to 35 parts by weight when the adhesion-preventive composition for unvulcanized rubber is taken as 100 parts by weight, the total weight ratio of the iron oxide and the iron sulfide to the total of the silicate, the iron oxide, and the iron sulfide is less than 2% by weight, and the surfactant contains a nonionic surfactant having an HLB of 3 to 13, so that the adhesion-preventive compositions for unvulcanized rubber satisfy both the anti-adhesion and disintegration properties that are the objective of the present application. On the other hand, as can be seen from Table 3, when the total weight ratio of iron oxide and iron sulfide to the total of silicate, the iron oxide, and the iron sulfide is 2% by weight or more (Comparative Examples 1 and 2), when there is no silicate (Comparative Examples 3 and 4), when there is no metal soap or wax (Comparative Example 5), when there is no nonionic surfactant (Comparative Examples 6 and 7), or when the HLB of the nonionic surfactant is not 3 to 13 (Comparative Examples 8 and 9), either one of the issues of the present application, anti-adhesion property or disintegration property, is not satisfied. [Industrial Applicability]
[0058] The anti-adhesive composition for unvulcanized rubber of the present invention is used in the production and processing of unvulcanized rubber products, and can prevent adhesion of rubber when unvulcanized rubber is stored in piles until it is transferred to the next process of molding, vulcanization, etc. In this case, the dried and solidified product of the anti-adhesive has good disintegratability, making it possible to reduce defects in rubber products.
Claims
1. An anti-adhesive composition for unvulcanized rubber, comprising an inorganic component, a surfactant, and a metal soap and / or a wax, The inorganic component essentially contains a silicate and at least one selected from iron oxide and iron sulfide, the silicate is 10 to 32.5 parts by weight, and the total amount of the metal soap and / or the wax is 10 to 65 parts by weight, based on 100 parts by weight of the adhesion preventive composition for unvulcanized rubber; the total weight ratio of the iron oxide and the iron sulfide to the total weight of the silicate, the iron oxide, and the iron sulfide is less than 2% by weight; The anti-adhesive composition for unvulcanized rubber essentially contains a nonionic surfactant having an HLB of 3 to 13 as determined by the Griffin method.
2. The adhesion inhibitor composition for unvulcanized rubber according to claim 1, further comprising a carbonate.
3. A method for producing adhesion-preventively treated unvulcanized rubber, comprising a treatment step of adhering the adhesion-preventive composition for unvulcanized rubber according to claim 1 or 2 to a surface of molded unvulcanized rubber.
Citation Information
Patent Citations
Antitack composition for unvulcanized rubber
JP1987032127A
Adhesion inhibitor for rubber
JP2002363532A
Adhesion-proof agent pack for unvulcanized rubber
JP2010247864A
Anti-sticking agent composition for unvulcanized rubber
JP2013209658A
Adhesion preventive for unvulcanized rubber and water dispersion of adhesion preventive for unvulcanized rubber
JP2020041089A
